Criminal liability of legal persons: a comparative study between Spain and Peru - Fernández Díaz, Carmen Rocío (2016)
This paper studies the criminal liability of legal persons, which has suffered a deep reform with the organic law 1/2015, after being introduced in Spain in 2010. This reform has brought important modifications and news, as the creation of an exemption of liability through the adoption of compliance programs, which supposes a change in the so called model of transfer of liability, that existed before. Parallel to this transformation in the Spanish criminal code, in Peru recently the law 30424 has come into forth, which contents a corporate liability model, very similar to the one foreseen in Spain. Both models of liability and the possibility of its exemption raise doubts about if they really tried to penalize legal persons or not.